Mood, anxiety, and alcohol use disorders and later cause-specific sick leave in young adult employees. (December 2016) - Torvik, Fartein; Reichborn-Kjennerud, Ted; Gjerde, Line; Knudsen, Gun; Ystrom, Eivind; Tambs, Kristian; Røysamb, Espen; Østby, Kristian; Ørstavik, Ragnhild
Abstract Background Mental disorders strongly influence work capability in young adults, but it is not clear which disorders that are most strongly associated with sick leave, and which diagnoses that are stated on the sick leave certificates. Better knowledge of the impairments associated with different mental disorders is needed for optimal planning of interventions and prioritization of health services. In the current study, we investigate the prospective associations between eight mood, anxiety, and alcohol use disorders, and later sick leave granted for mental, somatic, or any disorder. Methods Lifetime mental disorders were assessed by structured diagnostic interviews in 2, 178 young adults followed for eight years with registry data on sick leave. Relative risk ratios were estimated for the associations between each mental disorder and the different forms of sick leave. Results All included diagnoses were associated with later sick leave. In adjusted analyses, major depressive disorder and generalized anxiety disorder were the strongest predictors of sick leave granted for mental disorders, whereas social anxiety disorder and specific phobia were the strongest predictors of sick leave granted for somatic disorders. Specific phobia and major depressive disorder had the highest attributable fractions for all-cause sick leave. Conclusions Mood and anxiety disorders constituted independent risk factors for all cause sick leave, whereas alcohol use disorders seemed to be of less importance in young adulthood. Disorders characterised by distress were most strongly associated with sick leave granted for mental disorders, whereas disorders characterised by fear primarily predicted sick leave granted for somatic conditions. A large part of all sick leave is related to specific phobia, due to the high prevalence of this disorder. The impairment associated with this common disorder may be under-acknowledged, and it could decrease work capacity among individuals with somatic disorders. This disorder has good treatment response and may be overlooked as a target for interventions aimed at prevention of sick leave.